Chemical mechanical polishing composition and polishing method

By using a chemical mechanical polishing composition containing abrasive grains, liquid media, oxidants and nitrogen-containing heterocyclic compounds, the problem of silver residue and corrosion during the polishing process is solved, and high-speed polishing and high reflection of the silver polished surface are achieved. Excellent results.

CN119343748APending Publication Date: 2025-01-21JICC 02 LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380044924.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

As a wiring material, silver is prone to residue on the pattern during the grinding process, and the existing copper or aluminum polishing methods cannot effectively suppress silver corrosion or wear damage.

Method used

A composition for chemical mechanical grinding, which contains grinding particles, hydraulic media, oxidant and nitrogen -containing compounds. By adjusting the potential and component ratio Excellent effect.

Benefits of technology

The composition can grind the polished surface containing silver at high speed, reduce corrosion or grinding damage after grinding, and obtain results with excellent high reflective properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169377750000203
    Figure BDA0005169377750000203
  • Figure BDA0005169377750000221
    Figure BDA0005169377750000221
  • Figure BDA0005169377750000231
    Figure BDA0005169377750000231
Patent Text Reader

Abstract

Provided are: a chemical mechanical polishing composition which is capable of polishing a surface to be polished, which contains silver as a wiring material, at a high speed, and which is capable of obtaining a surface to be polished having excellent high reflection characteristics; and a polishing method using the chemical mechanical polishing composition. This composition for chemical mechanical polishing contains (A) abrasive grains, (B) a liquid medium, (C) an oxidizing agent, and (D) a nitrogen-containing heterocyclic compound, and is characterized in that: the absolute value of the zeptotatic potential of the component (A) in the composition for chemical mechanical polishing is 10 mV or more; when the content of the component (C) is Mc (mass%) and the content of the component (D) is Md (mass%), Mc / Md = 10-200.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a chemical mechanical polishing composition and a polishing method using the same. Background Art

[0002] Chemical Mechanical Polishing (hereinafter referred to as "CMP") is effectively used in semiconductor manufacturing processes, especially in planarization of interlayer insulating films, metal plug formation, and buried wiring (Damascene wiring) formation in multilayer wiring formation processes. CMP in such semiconductor manufacturing processes requires not only high-speed polishing of insulating materials such as silicon oxide, barrier materials such as tantalum nitride, and wiring materials such as aluminum or copper, but also polishing characteristics that achieve a balance between high flatness and low defects.

[0003] In recent years, research has been underway to replace copper with silver as a wiring material to obtain semiconductor devices with higher performance. Silver has the following characteristics: it has a lower resistivity and higher electromigration stability than copper. Therefore, silver may contribute to the high performance of semiconductor devices and can be expected to be an effective wiring material (for example, see Patent Documents 1 and 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Publication No. 2005-518669

[0007] Patent Document 2: Japanese Patent Publication No. 2014-507799 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, since silver has very different properties from copper, the existing copper wiring polishing slurry cannot be directly used. It is necessary to use a technology different from the existing copper or aluminum to suppress the silver residue (silver residue) on the wiring pattern and the corrosion or polishing damage of the wiring part caused by the chemical composition of the polishing liquid.

[0010] Some aspects of the present invention provide a chemical mechanical polishing composition that can polish a polished surface containing silver as a wiring material at a high speed and can obtain a polished surface having excellent high reflectivity, and a polishing method using the same.

[0011] Technical means of solving problems

[0012] One embodiment of the chemical mechanical polishing composition of the present invention comprises

[0013] (A) Abrasive particles,

[0014] (B) Liquid medium,

[0015] (C) an oxidizing agent, and

[0016] (D) Nitrogen-containing heterocyclic compounds

[0017] A chemical mechanical polishing composition, wherein

[0018] The absolute value of the zeta potential of the component (A) in the chemical mechanical polishing composition is 10 mV or more,

[0019] When the content of the (C) component is represented by Mc (mass %) and the content of the (D) component is represented by Md (mass %), Mc / Md=10-200.

[0020] In one embodiment of the chemical mechanical polishing composition,

[0021] The component (A) may have a functional group represented by the following general formula (1).

[0022] -SO3 - M + ……(1)

[0023] (M + represents a monovalent cation)

[0024] In one embodiment of the chemical mechanical polishing composition,

[0025] The zeta potential of the component (A) in the chemical mechanical polishing composition may be -10 mV or less.

[0026] In one embodiment of the chemical mechanical polishing composition,

[0027] The component (A) may have a functional group represented by the following general formula (2).

[0028] -COO - M + ……(2)

[0029] (M + represents a monovalent cation)

[0030] In one embodiment of the chemical mechanical polishing composition,

[0031] The zeta potential of the component (A) in the chemical mechanical polishing composition may be -10 mV or less.

[0032] In one embodiment of the chemical mechanical polishing composition,

[0033] The component (A) may have a functional group represented by the following general formula (3) or the following general formula (4).

[0034] -NR 1 R 2 ……(3)

[0035] -N + R 1 R 2 R 3 M - ……(4)

[0036] (In the above formula (3) and formula (4), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, or a substituted or unsubstituted hydrocarbon group; M - represents anion)

[0037] In one embodiment of the chemical mechanical polishing composition,

[0038] The zeta potential of the component (A) in the chemical mechanical polishing composition may be +10 mV or more.

[0039] In one embodiment of the chemical mechanical polishing composition,

[0040] The pH may be 1 or more and 6 or less.

[0041] In one embodiment of the chemical mechanical polishing composition,

[0042] The content of the component (A) may be 0.005 mass % to 15 mass % based on the total mass of the chemical mechanical polishing composition.

[0043] In one embodiment of the chemical mechanical polishing composition,

[0044] The component (D) may have an azole structure.

[0045] One aspect of the grinding method of the present invention includes:

[0046] A step of polishing a semiconductor substrate using any one of the chemical mechanical polishing compositions described above.

[0047] In one aspect of the grinding method,

[0048] The semiconductor substrate may include a portion containing silver.

[0049] Effects of the Invention

[0050] The chemical mechanical polishing composition of the present invention can polish a polished surface containing silver as a wiring material at a high speed, and can effectively reduce the occurrence of corrosion or polishing damage on the polished surface after polishing, thereby obtaining a polished surface with excellent high reflectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing a workpiece that is preferably used in the polishing method of this embodiment.

[0052] [ Figure 2 ] Figure 2 It is a cross-sectional view schematically showing the object to be processed when the first polishing step is completed.

[0053] [ Figure 3 ] Figure 3 It is a cross-sectional view schematically showing the object to be processed when the second polishing step is completed.

[0054] [ Figure 4 ] Figure 4 It is a perspective view schematically showing a chemical mechanical polishing apparatus. DETAILED DESCRIPTION

[0055] Hereinafter, preferred embodiments of the present invention will be described in detail. In addition, the present invention is not limited to the following embodiments, and includes various modifications that are implemented within the scope of the present invention.

[0056] In this specification, the term "wiring material" refers to conductive metal materials such as aluminum, copper, silver, gold, cobalt, titanium, ruthenium, and tungsten. The term "insulating film material" refers to materials such as silicon dioxide, silicon nitride, amorphous silicon, and hafnium oxide. The term "barrier metal material" refers to materials such as tantalum nitride and titanium nitride that are used in a stacked manner with wiring materials for the purpose of improving wiring reliability.

[0057] In this specification, the numerical range described using "X to Y" is interpreted as including the numerical value X as the lower limit and the numerical value Y as the upper limit.

[0058] 1. Chemical mechanical polishing composition

[0059] A chemical mechanical polishing composition according to one embodiment of the present invention comprises: (A) abrasive grains (also referred to as "component (A)" in this specification), (B) a liquid medium (also referred to as "component (B)" in this specification), (C) an oxidizing agent (also referred to as "component (C)" in this specification), and (D) a nitrogen-containing heterocyclic compound (also referred to as "component (D)" in this specification), wherein the absolute value of the zeta potential of component (A) in the chemical mechanical polishing composition is greater than or equal to 10 mV. The components contained in the chemical mechanical polishing composition according to this embodiment are described in detail below.

[0060] 1.1.(A)Ingredients

[0061] The chemical mechanical polishing composition of this embodiment contains (A) abrasive grains. The component (A) is not particularly limited as long as it is abrasive grains having an absolute value of the zeta potential in the chemical mechanical polishing composition of 10 mV or more.

[0062] The abrasive grains can be produced by the method described in Japanese Patent Laid-Open No. 2007-153732 or Japanese Patent Laid-Open No. 2013-121631, for example. By modifying at least a portion of the surface of the abrasive grains obtained in the above manner with functional groups, abrasive grains having an absolute value of zeta potential of 10 mV or more in the chemical mechanical polishing composition can be produced.

[0063] The absolute value of the zeta potential of the component (A) in the chemical mechanical polishing composition is 10 mV or more, preferably 15 mV or more, and more preferably 20 mV or more. The absolute value of the zeta potential of the component (A) in the chemical mechanical polishing composition is preferably 40 mV or less. If the absolute value of the zeta potential of the component (A) in the chemical mechanical polishing composition is within the range, the dispersibility of the abrasive particles in the chemical mechanical polishing composition is improved by the electrostatic repulsion between the abrasive particles. As a result, the abrasive surface can be polished at a high speed while reducing the generation of polishing damage or depression on the polished surface.

[0064] The average secondary particle size of (A) component is preferably more than 5nm and less than 200nm, more preferably more than 10nm and less than 100nm. If the average secondary particle size of (A) component is within the range, sufficient polishing rate can be obtained sometimes, and a chemical mechanical polishing composition with excellent stability without particle sedimentation and separation can be obtained. In addition, the average secondary particle size of (A) component can be obtained by, for example, using "Zetasizer Ultra" manufactured by Malvern (Malvern) and by calculating and obtaining by dynamic light scattering.

[0065] The shape of the (A) component is not particularly limited, and may be spherical or non-spherical. In the case where the shape of the (A) component is non-spherical, it is preferably a shape having a plurality of protrusions on the surface. The protrusions described herein refer to protrusions having a sufficiently small height and width compared to the particle size of the abrasive grains. The number of protrusions on the surface of the (A) component is preferably an average of three or more per abrasive grain, and more preferably five or more. The shape of the (A) component having a plurality of protrusions on the surface can also be described as abrasive grains having a special shape such as the so-called confetti-like. By having such a special shape of the (A) component, the polishing speed of the polished surface containing silver is improved compared to the case of using spherical abrasive grains. In addition, by having such a special shape of the (A) component, the surface area becomes larger, and the reactivity with the compound having a functional group described later is improved. As a result, the absolute value of the zeta potential of the (A) component in the chemical mechanical polishing composition becomes larger, and the dispersibility is improved. As a result, the polished surface can be polished at a high speed while reducing the generation of polishing damage or depressions on the polished surface.

[0066] The (A) component preferably contains silicon oxide as a main component. When the (A) component contains silicon oxide as a main component, it may also contain other components. As other components, aluminum compounds, silicon compounds, etc. can be listed. By the (A) component also containing aluminum compounds or silicon compounds, the surface hardness of the (A) component can be reduced, so there is a situation that the grinding damage or the generation of depressions in the ground surface can be further reduced.

[0067] Examples of aluminum compounds include aluminum hydroxide, aluminum oxide (alumina), aluminum chloride, aluminum nitride, aluminum acetate, aluminum phosphate, aluminum sulfate, sodium aluminate, potassium aluminate, etc. On the other hand, examples of silicon compounds include silicon nitride, silicon carbide, silicates, silicones, silicone resins, etc.

[0068] The component (A) is preferably an abrasive grain whose surface is at least partially modified by a functional group. The abrasive grain whose surface is at least partially modified by a functional group has a larger absolute value of the zeta potential than the abrasive grain whose surface is not modified by a functional group in the pH range of 1 to 6, and the electrostatic repulsion between the abrasive grains increases. As a result, since the dispersibility of the abrasive grains in the chemical mechanical polishing composition is improved, high-speed polishing can be performed while reducing the generation of polishing damage or depressions on the polished surface.

[0069] Hereinafter, the specific form of the component (A) will be described in detail.

[0070] 1.1.1. First form

[0071] As a first aspect of the component (A), there can be mentioned abrasive grains having a functional group represented by the following general formula (1).

[0072] -SO3 - M + ·····(1)

[0073] (M + represents a monovalent cation)

[0074] In the formula (1), M + The monovalent cations represented are not limited to these, and examples thereof include H + , Li + 、Na + , K + NH4 + That is, the functional group represented by the general formula (1) can also be referred to as "at least one functional group selected from the group consisting of a sulfonic group and a salt thereof". Here, the so-called "sulfonic group salt" refers to a functional group formed by reacting Li + 、Na + , K + NH4 + The first form of the component (A) is an abrasive grain having a functional group represented by the general formula (1) fixed to its surface via a covalent bond, and does not include abrasive grains having a compound having a functional group represented by the general formula (1) physically or ionically adsorbed on its surface.

[0075] The first form of component (A) can be manufactured in the following manner. First, silicon oxide particles are prepared by the method described in Japanese Patent Laid-Open No. 2007-153732 or Japanese Patent Laid-Open No. 2013-121631. Then, the silicon oxide particles and the mercapto-containing silane coupling agent are fully stirred in an acidic medium, thereby covalently bonding the mercapto-containing silane coupling agent to the surface of the silicon oxide particles. Here, as mercapto-containing silane coupling agents, for example, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, etc. can be listed. Next, an appropriate amount of hydrogen peroxide is added and allowed to stand sufficiently, thereby obtaining abrasive particles having the functional group represented by the general formula (1).

[0076] The zeta potential of the first form (A) component is a negative potential in the chemical mechanical polishing composition, and the negative potential is preferably below -10mV, more preferably below -15mV, and particularly preferably below -20mV. If the zeta potential of the first form (A) component is within the range, there is a situation in which the particles can be effectively prevented from agglomerating with each other by the electrostatic repulsion between the abrasive particles, and the substrate with a positive charge can be selectively polished during chemical mechanical polishing. In addition, as a zeta potential measuring device, "ELSZ-2000ZS" manufactured by Otsuka Electronics Co., Ltd., "Zetasizer nano zs" manufactured by Malvern, etc. can be cited. The zeta potential of the first form (A) component can be adjusted by appropriately increasing or decreasing the amount of the mercapto-containing silane coupling agent, etc.

[0077] In the case where the chemical mechanical polishing composition of the present embodiment contains the first form of component (A), when the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the first form of component (A) is preferably 0.005 mass% or more, more preferably 0.1 mass% or more, and particularly preferably 0.5 mass% or more. When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the first form of component (A) is preferably 15 mass% or less, more preferably 8 mass% or less, and particularly preferably 5 mass% or less. If the content of the first form of component (A) is within the range, there is a case where the polished surface containing silver can be polished at a high speed and the storage stability of the chemical mechanical polishing composition becomes good.

[0078] 1.1.2. Second Form

[0079] As a second aspect of the component (A), abrasive grains having a functional group represented by the following general formula (2) can be mentioned.

[0080] -COO - M + ·····(2)

[0081] (M + represents a monovalent cation)

[0082] In the formula (2), M + The monovalent cations represented are not limited to these, and examples thereof include H + , Li + 、Na + , K + NH4 + That is, the functional group represented by the general formula (2) can also be referred to as "at least one functional group selected from the group consisting of a carboxyl group and a salt thereof". Here, the so-called "salt of a carboxyl group" refers to a functional group formed by reacting Li+ 、Na + , K + NH4 + The second aspect of the component (A) is an abrasive grain having a functional group represented by the general formula (2) fixed to its surface via a covalent bond, and does not include abrasive grains having a compound having a functional group represented by the general formula (2) physically or ionically adsorbed on its surface.

[0083] The second form of component (A) can be manufactured in the following manner. First, silicon oxide particles are prepared by the method described in Japanese Patent Publication No. 2007-153732 or Japanese Patent Publication No. 2013-121631. Then, the silicon oxide particles and a silane coupling agent containing a carboxylic anhydride are fully stirred in an alkaline medium so that the silane coupling agent containing a carboxylic anhydride is covalently bonded to the surface of the silicon oxide particles, thereby obtaining abrasive particles having a functional group represented by the general formula (2). Here, as a silane coupling agent containing a carboxylic anhydride, for example, 3-(triethoxysilyl)propyl succinic anhydride can be listed.

[0084] The zeta potential of the (A) component of the second form is a negative potential in the chemical mechanical polishing composition, and the negative potential is preferably below -10mV, more preferably below -15mV, and particularly preferably below -20mV. If the zeta potential of the (A) component of the second form is within the range, there is a situation where the particles can be effectively prevented from agglomerating with each other by the electrostatic repulsion between the abrasive particles, and a substrate with a positive charge can be selectively polished during chemical mechanical polishing. In addition, the zeta potential measuring device can use the device described in the first form. The zeta potential of the (A) component of the second form can be adjusted by appropriately increasing or decreasing the amount of the silane coupling agent containing carboxylic anhydride, etc.

[0085] In the case where the chemical mechanical polishing composition of the present embodiment contains the second form of the component (A), when the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the second form of the component (A) is preferably 0.005 mass% or more, more preferably 0.1 mass% or more, and particularly preferably 0.5 mass% or more. When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the second form of the component (A) is preferably 15 mass% or less, more preferably 8 mass% or less, and particularly preferably 5 mass% or less. If the content of the second form of the component (A) is within the range, there is a case where the polished surface containing silver can be polished at a high speed and the storage stability of the chemical mechanical polishing composition becomes good.

[0086] 1.1.3. Third Form

[0087] As a third aspect of the component (A), there can be mentioned abrasive grains having a functional group represented by the following general formula (3) or the following general formula (4).

[0088] -NR 1 R 2 ·····(3)

[0089] -N + R 1 R 2 R 3 M - ·····(4)

[0090] (In the above formula (3) and the above formula (4), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, or a substituted or unsubstituted hydrocarbon group; M - represents anion)

[0091] The functional group represented by the general formula (3) is an amino group, and the functional group represented by the general formula (4) is a salt of an amino group. Therefore, the functional group represented by the general formula (3) and the functional group represented by the general formula (4) can be collectively referred to as "at least one functional group selected from the group consisting of an amino group and a salt thereof". The (A) component of the third form is an abrasive grain having a functional group represented by the general formula (3) or the general formula (4) fixed to its surface via a covalent bond, and does not include abrasive grains having a compound having a functional group represented by the general formula (3) or the general formula (4) physically or ionically adsorbed on its surface.

[0092] In the formula (4), M - The anions represented are not limited to these, for example, in addition to OH - 、F - , Cl - Br - ,I - , CN - In addition to the anions, anions derived from acidic compounds can also be mentioned.

[0093] In the formula (3) and the formula (4), R 1 ~R 3 Each independently represents a hydrogen atom, or a substituted or unsubstituted hydrocarbon group, but R 1 ~R 3 Two or more of them may also be bonded to form a ring structure.

[0094] As R 1 ~R 3The hydrocarbon group represented may be any of an aliphatic hydrocarbon group, an aromatic hydrocarbon group, an aromatic aliphatic hydrocarbon group or an alicyclic hydrocarbon group. In addition, the aliphatic of the aliphatic hydrocarbon group and the aromatic aliphatic hydrocarbon group may be saturated or unsaturated, and may be straight-chain or branched. Examples of these hydrocarbon groups include straight-chain, branched, and cyclic alkyl, alkenyl, aralkyl, and aryl groups.

[0095] The alkyl group is preferably a lower alkyl group having 1 to 6 carbon atoms, and more preferably a lower alkyl group having 1 to 4 carbon atoms. Examples of such an alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, tert-pentyl, neopentyl, n-hexyl, isohexyl, sec-hexyl, tert-hexyl, cyclopentyl, and cyclohexyl.

[0096] The alkenyl group is preferably a lower alkenyl group having 1 to 6 carbon atoms, and more preferably a lower alkenyl group having 1 to 4 carbon atoms. Examples of such alkenyl groups include vinyl, n-propenyl, isopropenyl, n-butenyl, isobutenyl, sec-butenyl, and tert-butenyl.

[0097] The aralkyl group is preferably an aralkyl group having 7 to 12 carbon atoms. Examples of such an aralkyl group include benzyl, phenethyl, phenylpropyl, phenylbutyl, phenylhexyl, methylbenzyl, methylphenethyl, and ethylbenzyl.

[0098] The aryl group is preferably an aryl group having 6 to 14 carbon atoms. Examples of such an aryl group include phenyl, o-tolyl, m-tolyl, p-tolyl, 2,3-xylyl, 2,4-xylyl, 2,5-xylyl, 2,6-xylyl, 3,5-xylyl, naphthyl, and anthracenyl.

[0099] The aromatic ring of the aryl group and aralkyl group may have, as a substituent, a lower alkyl group such as a methyl group or an ethyl group, a halogen atom, a nitro group, an amino group, a hydroxyl group or the like.

[0100] The third form of component (A) can be manufactured in the following manner. First, silicon oxide particles are prepared by the method described in Japanese Patent Publication No. 2007-153732 or Japanese Patent Publication No. 2013-121631. Then, the silicon oxide particles and an amino-containing silane coupling agent are fully stirred in an acidic medium so that the amino-containing silane coupling agent is covalently bonded to the surface of the silicon oxide particles, thereby obtaining abrasive particles having a functional group represented by the general formula (3) or the general formula (4). Here, as the amino-containing silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, etc. can be listed.

[0101] The zeta potential of the (A) component of the third form is a positive potential in the chemical mechanical polishing composition, and the positive potential is preferably above +10mV, more preferably above +15mV, and particularly preferably above +20mV. If the zeta potential of the (A) component of the third form is within the range, there is a situation where the particles can be effectively prevented from agglomerating with each other by the electrostatic repulsion between the abrasive particles, and the substrate with a negative charge can be selectively polished during chemical mechanical polishing. In addition, the zeta potential measuring device can use the device described in the first form. The zeta potential of the (A) component of the third form can be adjusted by appropriately increasing or decreasing the amount of the amino-containing silane coupling agent or the like.

[0102] In the case where the chemical mechanical polishing composition of the present embodiment contains the third form of the component (A), when the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the third form of the component (A) is preferably 0.005 mass% or more, more preferably 0.1 mass% or more, and particularly preferably 0.5 mass% or more. When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the third form of the component (A) is preferably 15 mass% or less, more preferably 8 mass% or less, and particularly preferably 5 mass% or less. If the content of the third form of the component (A) is within the range, there is a case where the polished surface containing silver can be polished at a high speed and the storage stability of the chemical mechanical polishing composition becomes good.

[0103] 1.2. (B) Liquid medium

[0104] The chemical mechanical polishing composition of the present embodiment contains (B) a liquid medium. As the (B) component, water, a mixed medium of water and alcohol, a mixed medium containing water and an organic solvent miscible with water, etc. can be cited. Among these, it is preferred to use a mixed medium of water or water and alcohol, and more preferably to use water. As water, there is no particular restriction, but pure water is preferred. Water can be prepared as the remainder of the constituent materials of the chemical mechanical polishing composition, and there is no particular restriction on the content of water.

[0105] 1.3. (C) Oxidants

[0106] The chemical mechanical polishing composition of the present embodiment contains (C) an oxidant. By containing (C) component, the polished surface containing silver can be oxidized to form a fragile modified layer, thereby polishing the polished surface at a high speed. As (C) component, organic peroxides such as hydrogen peroxide, peracetic acid, perbenzoic acid, tert-butyl hydroperoxide, permanganate compounds such as potassium permanganate, dichromate compounds such as potassium dichromate, hydrohalide acids such as potassium iodate, nitric acid compounds such as ferric nitrate, perchloric acid and other hydrohalide acids, persulfates such as ammonium persulfate, and heteropolyacids can be listed. Among these, organic peroxides are preferred, and hydrogen peroxide is more preferred. These oxidants can be used alone or in combination of two or more.

[0107] When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the component (C) in the chemical mechanical polishing composition of the present embodiment is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, and particularly preferably 0.4 mass% or more. When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the component (C) is preferably 5 mass% or less, more preferably 3 mass% or less, and particularly preferably 1 mass% or less.

[0108] 1.4. (D) Nitrogen-containing heterocyclic compounds

[0109] The chemical mechanical polishing composition of the present embodiment contains (D) a nitrogen-containing heterocyclic compound. The (D) component is adsorbed on the polished surface containing silver, thereby protecting the polished surface. As a result, the generation of corrosion or polishing damage on the polished surface after polishing can be effectively reduced, so that a polished surface with excellent high reflectivity can be obtained. The so-called nitrogen-containing heterocyclic compound refers to an organic compound having at least one nitrogen atom and containing at least one heterocyclic ring selected from a heterocyclic five-membered ring and a heterocyclic six-membered ring. As nitrogen-containing heterocyclic rings, there can be listed: heterocyclic five-membered rings such as pyrrole structure, imidazole structure, and triazole structure; heterocyclic six-membered rings such as pyridine structure, pyrimidine structure, pyridazine structure, and pyrazine structure. These heterocyclic rings can also form condensed rings. Specifically, there can be listed: indole structure, isoindole structure, benzimidazole structure, benzotriazole structure, quinoline structure, isoquinoline structure, quinazoline structure, cinnoline structure, phthalazine structure, quinoxaline structure, acridine structure, etc. Among the heterocyclic compounds having such a structure, preferred are heterocyclic compounds having a pyridine structure, a quinoline structure, a benzimidazole structure, and a benzotriazole structure.

[0110] Specific examples of nitrogen-containing heterocyclic compounds include aziridine, pyridine, pyrimidine, pyrrolidine, piperidine, pyrazine, triazine, pyrrole, imidazole, indole, quinoline, isoquinoline, benzisoquinoline, purine, pteridine, triazole, triazolidine, benzotriazole, carboxybenzotriazole, and derivatives having these skeletons. Among these, preferably a compound having an azole structure, more preferably at least one selected from triazole, benzotriazole, carboxybenzotriazole, and derivatives having these skeletons. These nitrogen-containing heterocyclic compounds can be used alone or in combination of two or more.

[0111] When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the component (D) in the chemical mechanical polishing composition of the present embodiment is preferably 0.001 mass% or more, more preferably 0.005 mass% or more, and particularly preferably 0.01 mass% or more. When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the component (D) is preferably 1 mass% or less, more preferably 0.1 mass% or less, and particularly preferably 0.07 mass% or less.

[0112] In addition, the chemical mechanical polishing composition of the present embodiment needs to set the content ratio of the component (C) to the component (D) within a specified range. In the chemical mechanical polishing composition of the present embodiment, when the content of the component (C) is Mc (mass %) and the content of the component (D) is Md (mass %), the value of Mc / Md is 10 or more, preferably 11 or more, and more preferably 12 or more. In addition, the value of Mc / Md is 200 or less, preferably 190 or less, and more preferably 185 or less. If the value of Mc / Md is within the range, the balance between the effect of high-speed polishing of the polished surface containing silver and the effect of reducing the generation of corrosion or polishing damage on the polished surface after polishing becomes good, and these effects can coexist.

[0113] 1.5. Other ingredients

[0114] The chemical mechanical polishing composition of this embodiment may contain, in addition to the above-mentioned components, an organic acid and its salt, a phosphoric acid ester, a water-soluble polymer, a surfactant, an inorganic acid and its salt, a basic compound, and the like as necessary.

[0115] <Organic acids and their salts>

[0116] The chemical mechanical polishing composition of this embodiment may also contain at least one selected from the group consisting of organic acids and salts thereof (hereinafter also referred to as "organic acid (salt)"). Organic acids and salts thereof may further increase the polishing rate of the polished surface containing silver through a synergistic effect with component (A).

[0117] As organic acids and salts thereof, compounds having a carboxyl group and compounds having a sulfonic group are preferred. As compounds having a carboxyl group, for example, stearic acid, lauric acid, oleic acid, myristic acid, alkenyl succinic acid, lactic acid, tartaric acid, fumaric acid, glycolic acid, phthalic acid, maleic acid, formic acid, acetic acid, oxalic acid, citric acid, malic acid, malonic acid, glutaric acid, succinic acid, benzoic acid, quinolinic acid, quinaldic acid, amidosulfuric acid, propionic acid, trifluoroacetic acid; amino acids such as glycine, alanine, aspartic acid, glutamic acid, lysine, arginine, tryptophan, dodecylaminoethylaminoethylglycine, aromatic amino acids, heterocyclic amino acids; imino acids such as alkyl imino dicarboxylic acids; and salts thereof. As compounds having a sulfonic group, for example, alkyl benzene sulfonic acids such as dodecylbenzenesulfonic acid and p-toluenesulfonic acid; alkyl naphthalenesulfonic acids such as butylnaphthalenesulfonic acid; α-olefin sulfonic acids such as tetradecenesulfonic acid, etc. can be listed. These compounds may be used alone or in combination of two or more.

[0118] When the chemical mechanical polishing composition of this embodiment contains an organic acid (salt), when the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the organic acid (salt) is preferably 0.001 mass% or more, and more preferably 0.01 mass% or more. When the total mass of the chemical mechanical polishing composition is set to 100 mass%, the content of the organic acid (salt) is preferably 5 mass% or less, and more preferably 1 mass% or less.

[0119] <Phosphate ester>

[0120] The chemical mechanical polishing composition of this embodiment may contain a phosphoric acid ester. The phosphoric acid ester may be adsorbed on the surface of the polishing surface containing silver, thereby enhancing the effect of reducing the occurrence of dishing.

[0121] Generally speaking, phosphate ester is a general term for compounds having a structure in which all or part of the three hydrogen atoms in phosphoric acid (O=P(OH)3) are replaced by organic groups. Among phosphate esters, polyoxyethylene alkyl ether phosphate esters are preferably used in terms of their particularly high effect in reducing the occurrence of pits. Polyoxyethylene alkyl ether phosphate esters are nonionic anionic surfactants and can be represented by the following general formula (5).

[0122] [R 4 -O-(CH2CH2O) n ] m -H 3-m PO 4-m ·····(5)

[0123] In the formula (5), R 4 represents a hydrocarbon group having 10 or more carbon atoms, n is 5 or more and less than 30, and m is 1 or 2. 4The hydrocarbon group having 10 or more carbon atoms represented by is preferably an alkyl group having 10 or more carbon atoms, and more preferably an alkyl group having 10 to 30 carbon atoms. Specific examples of the alkyl group having 10 to 30 carbon atoms include decyl, isodecyl, lauryl, tridecyl, cetyl, oleyl, and stearyl. In the formula (5), when m=2, the two R 4 The molecular weight of such polyoxyethylene alkyl ether phosphate is usually 400 or more.

[0124] As specific examples of polyoxyethylene alkyl ether phosphates, there can be listed: phosphate monoesters of polyoxyethylene decyl ether, phosphate diesters of polyoxyethylene decyl ether, phosphate monoesters of polyoxyethylene isodecyl ether, phosphate diesters of polyoxyethylene isodecyl ether, phosphate monoesters of polyoxyethylene lauryl ether, phosphate diesters of polyoxyethylene lauryl ether, phosphate monoesters of polyoxyethylene tridecyl ether, phosphate diesters of polyoxyethylene tridecyl ether, phosphate monoesters of polyoxyethylene allyl phenyl ether, phosphate diesters of polyoxyethylene allyl phenyl ether, etc. These can be used alone or in combination of two or more. In addition, there are monoesters, diesters, etc. in these polyoxyethylene alkyl ether phosphates, but in the chemical mechanical polishing composition of the present embodiment, the monoesters and diesters can be used alone or as a mixture.

[0125] When the chemical mechanical polishing composition of this embodiment contains a phosphate ester, the content of the phosphate ester is preferably 0.001% by mass or more, and more preferably 0.002% by mass or more, when the total mass of the chemical mechanical polishing composition is 100% by mass. When the total mass of the chemical mechanical polishing composition is 100% by mass, the content of the phosphate ester is preferably 0.1% by mass or less, and more preferably 0.01% by mass or less.

[0126] <Water-soluble polymer>

[0127] The chemical mechanical polishing composition of this embodiment may contain a water-soluble polymer. The water-soluble polymer may be adsorbed on the surface of the polishing surface containing silver to reduce polishing friction and thereby reduce the occurrence of depressions on the polishing surface.

[0128] Specific examples of the water-soluble polymer include polycarboxylic acid, polystyrenesulfonic acid, polyacrylic acid, polymethacrylic acid, polyether, polyacrylamide, polyvinyl alcohol, polyvinylpyrrolidone, polyethyleneimine, polyallylamine, hydroxyethylcellulose, etc. These may be used alone or in combination of two or more.

[0129] The weight average molecular weight (Mw) of the water-soluble polymer is preferably 5,000 to 800,000, more preferably 7,000 to 100,000. Here, the "weight average molecular weight" refers to the weight average molecular weight in terms of polyethylene glycol measured by gel permeation chromatography (GPC).

[0130] When the chemical mechanical polishing composition of this embodiment contains a water-soluble polymer, the content of the water-soluble polymer is preferably 0.001% by mass or more, more preferably 0.002% by mass or more, based on the total mass of the chemical mechanical polishing composition being 100% by mass. When the total mass of the chemical mechanical polishing composition being 100% by mass, the content of the water-soluble polymer is preferably 0.1% by mass or less, more preferably 0.01% by mass or less.

[0131] <Surfactant>

[0132] There are no particular restrictions on the surfactant, and anionic surfactants, cationic surfactants, nonionic surfactants, etc. can be used. Examples of anionic surfactants include sulfates such as alkyl ether sulfates and polyoxyethylene alkylphenyl ether sulfates; fluorine-containing surfactants such as perfluoroalkyl compounds, etc. Examples of cationic surfactants include aliphatic amine salts and aliphatic ammonium salts. Examples of nonionic surfactants include nonionic surfactants having triple bonds such as acetylene glycol, acetylene glycol ethylene oxide adducts, and acetylene alcohol; polyethylene glycol-type surfactants, etc. These surfactants can be used alone or in combination of two or more.

[0133] <Inorganic acids and their salts>

[0134] The inorganic acid is preferably at least one selected from hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid. The inorganic acid may also form a salt with a base added separately to the chemical mechanical polishing composition.

[0135] <Basic compounds>

[0136] As the basic compound, organic bases and inorganic bases can be cited. As the organic base, amines are preferred, and examples thereof include triethylamine, monoethanolamine, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, benzylamine, methylamine, ethylenediamine, diglycolamine, isopropylamine, etc. As the inorganic base, ammonia, potassium hydroxide, sodium hydroxide, etc. can be cited, for example. Among these basic compounds, ammonia and potassium hydroxide are preferred. These basic compounds can be used alone or in combination of two or more.

[0137] 1.6.pH

[0138] The pH of the chemical mechanical polishing composition of this embodiment is preferably from 1 to 6, more preferably from 1 to 5, and particularly preferably from 2 to 4. When the pH is within the above range, the absolute value of the zeta potential of the component (A) in the chemical mechanical polishing composition increases, thereby improving dispersibility, and thus high-speed polishing can be performed while reducing the occurrence of polishing scratches or pits on the polished surface containing silver.

[0139] The pH of the chemical mechanical polishing composition of this embodiment can be adjusted by appropriately increasing or decreasing the content of the organic acid and its salt, the inorganic acid and its salt, and the basic compound as necessary.

[0140] In the present invention, pH refers to a hydrogen ion index, and its value can be measured under the conditions of 25° C. and 1 atmosphere using a commercially available pH meter (for example, a desktop pH meter manufactured by Horiba, Ltd.).

[0141] 1.7. Purpose

[0142] The chemical mechanical polishing composition of this embodiment is suitable as a polishing material for chemical mechanical polishing of semiconductor substrates having various materials constituting semiconductor devices. The semiconductor substrate to be polished may have, in addition to silver as a conductive metal, an insulating film material such as silicon oxide, silicon nitride, amorphous silicon, polycrystalline silicon, or a barrier metal material such as titanium, titanium nitride, and tantalum nitride.

[0143] The polishing object of the chemical mechanical polishing composition of this embodiment is preferably a semiconductor substrate including a portion containing silver. As a specific example of such a semiconductor substrate, for example, a substrate having a silver film as a conductive metal applied thereon may be cited. Figure 1 A semiconductor substrate having a tantalum nitride film as a barrier metal and a silicon oxide film as an insulating film as shown. The chemical mechanical polishing composition of this embodiment can polish such a semiconductor substrate at a high speed, and can effectively reduce the occurrence of corrosion or polishing damage on the polished surface after polishing, so that a polished surface with excellent high reflectivity can be obtained.

[0144] 1.8. Preparation method of chemical mechanical polishing composition

[0145] The chemical mechanical polishing composition of this embodiment can be prepared by dissolving or dispersing the components in a liquid medium such as water. The method of dissolving or dispersing is not particularly limited, and any method can be applied as long as it can be uniformly dissolved or dispersed. In addition, there is no particular limitation on the mixing order and mixing method of the components.

[0146] The chemical mechanical polishing composition of this embodiment may be prepared as a concentrated stock solution and diluted with a liquid medium such as water before use.

[0147] 2. Grinding method

[0148] The polishing method of one embodiment of the present invention includes a step of polishing a semiconductor substrate using the chemical mechanical polishing composition. The semiconductor substrate preferably includes a portion containing silver. Since the chemical mechanical polishing composition can polish the polished surface containing silver at a high speed and can effectively reduce the corrosion or polishing damage on the polished surface after polishing, a polished surface with excellent high reflective properties can be obtained. The polished surface may also include a barrier metal film containing tantalum or titanium and / or an insulating film of silicon oxide or hafnium oxide. Below, a specific example of the polishing method of this embodiment is described in detail using the accompanying drawings.

[0149] 2.1. Object to be processed

[0150] Figure 1 1 is a cross-sectional view schematically showing a workpiece to be processed that is preferably used in the polishing method of this embodiment. The workpiece 100 is formed by passing through the following steps (1) to (4).

[0151] (1) First, Figure 1 As shown, a substrate 10 is prepared. The substrate 10 may include, for example, a silicon substrate and a silicon oxide film formed thereon. Furthermore, functional elements such as transistors (not shown) may be formed on the substrate 10. Next, a silicon oxide film 12 as an insulating film is formed on the substrate 10 using a thermal oxidation method.

[0152] (2) Next, a tantalum nitride film 14 is formed on the silicon oxide film 12. The tantalum nitride film 14 can be formed, for example, by chemical vapor deposition (CVD) or physical vapor deposition (PVD).

[0153] (3) Next, a photosensitive resist film is formed on the tantalum nitride film 14 using a spin coater, and selectively exposed and developed using a photomask. Next, plasma is irradiated to etch the portion without the resist. Thereafter, the protected resist is removed.

[0154] (4) Then, the physical vapor deposition method (PVD) is used to deposit The silver film 16. The object to be processed 100 can be manufactured by going through the above steps (1) to (4).

[0155] 2.2. Grinding method

[0156] 2.2.1. First grinding step

[0157] Figure 2Schematically shows a cross-sectional view of the object 100 to be processed at the end of the first polishing step. Figure 2 As shown in FIG. 1 , the first polishing step is a step of roughly polishing the silver film 16 using a chemical mechanical polishing composition that can polish the silver film 16 at a high speed. In the first polishing step, since a chemical mechanical polishing composition that can polish the silver film at a high speed is used, the surface of the silver film 16 may be formed as follows: Figure 2 Surface defects like the one shown are called pits.

[0158] 2.2.2. Second grinding process

[0159] Figure 3 Schematically shows a cross-sectional view of the object 100 to be processed at the end of the second polishing step. Figure 3 As shown in FIG. 1 , the second polishing step is a step of polishing the tantalum nitride film 14 and the silver film 16 using the chemical mechanical polishing composition (of the present invention) to make them flat. The chemical mechanical polishing composition (of the present invention) can control the polishing speed of the tantalum nitride film 14 and the silver film 16 in a well-balanced manner, thereby reducing the occurrence of depressions in the silver film 16, and polishing the exposed tantalum nitride film 14 and the silver film 16 at a high speed and in a well-balanced manner, thereby making them flat. In addition, the chemical mechanical polishing composition (of the present invention) can reduce the occurrence of polishing damage on the polished surface because the dispersibility of the component (A) is good.

[0160] 2.3. Chemical Mechanical Polishing Device

[0161] In the first grinding step and the second grinding step, for example, Figure 4 The grinding device 200 is shown. Figure 4 2 is a perspective view schematically showing a polishing device 200. The first polishing step and the second polishing step are performed by supplying a slurry (chemical mechanical polishing composition) 44 from a slurry supply nozzle 42, and rotating a turntable 48 to which a polishing pad 46 is attached while a carrier head 52 holding a semiconductor substrate 50 is brought into contact with the turntable 48. Figure 4 In the figure, a water supply nozzle 54 and a dresser 56 are also shown.

[0162] The polishing load of the carrier head 52 can be selected in the range of 0.7 psi to 70 psi, preferably 1.5 psi to 35 psi. In addition, the rotation speed of the turntable 48 and the carrier head 52 can be appropriately selected in the range of 10 rpm to 400 rpm, preferably 30 rpm to 150 rpm. The flow rate of the slurry (chemical mechanical polishing composition) 44 supplied from the slurry supply nozzle 42 can be selected in the range of 10 mL / min to 1,000 mL / min, preferably 50 mL / min to 400 mL / min.

[0163] As commercially available polishing devices, for example, there are: model "EPO-112" and "EPO-222" manufactured by EBARA Manufacturing Co., Ltd.; model "LGP-510" and "LGP-552" manufactured by Lapmaster SFT; model "Mirra" and "Reflexion" manufactured by Applied Materials; model "POLI-400L" manufactured by G&P TECHNOLOGY; model "Reflexion LK" manufactured by AMAT, etc.

[0164] 3. Example

[0165] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples. In addition, "parts" and "%" in the present examples are based on mass unless otherwise specified.

[0166] 3.1. Preparation of abrasive particles

[0167] <Preparation of Abrasive Grains A>

[0168] 5 kg of high-purity colloidal silica (code: PL-1; silica concentration: 12% by mass) manufactured by Fuso Chemical Industry Co., Ltd. was mixed with 6 g of 3-mercaptopropyltrimethoxysilane and heated under reflux for 2 hours to obtain a thiolated silica sol. Hydrogen peroxide was added to the silica sol and heated under reflux for 8 hours to oxidize the surface of the silica particles and fix the sulfonic groups. In this way, a dispersion containing 12% by mass of abrasive particles A having an average primary particle size of 20 nm and an average secondary particle size of 38 nm and having the silica surface modified with sulfonic groups was obtained.

[0169] <Preparation of Abrasive Grains B>

[0170] 5 kg of high-purity colloidal silica (code: PL-3; silica concentration: 20% by mass) manufactured by Fuso Chemical Industry Co., Ltd. was mixed with 6 g of 3-mercaptopropyltrimethoxysilane and heated under reflux for 2 hours to obtain a thiolated silica sol. Hydrogen peroxide was added to the silica sol and heated under reflux for 8 hours to oxidize the surface of the silica particles and fix the sulfonic groups. In this way, a dispersion containing 20% ​​by mass of abrasive particles B having an average primary particle size of 45 nm and an average secondary particle size of 68 nm and silica surfaces modified with sulfonic groups was obtained.

[0171] <Preparation of Abrasive Grains C>

[0172] After dispersing 900 g of high-purity colloidal silica (code: PL-3; silica concentration of 20% by mass) manufactured by Fuso Chemical Industries, Ltd. in a mixed solvent of 100 g of pure water and 2850 g of methanol, 50 g of 29% ammonia water was added. 40.0 g of 3-(triethoxysilyl)propyl succinic anhydride was added to the dispersion, and refluxed at boiling point for 6 hours. Thereafter, pure water was added to maintain the volume of the dispersion while replacing methanol and ammonia with water. When the pH of the dispersion was below 8.5 and the tower top temperature reached 100°C, the addition of pure water was terminated. The dispersion was placed so that the temperature was below 30°C. In this way, a dispersion containing 14% by mass of abrasive particles C was obtained, in which the average primary particle size was 47 nm, the average secondary particle size was 69 nm, and the silica surface was modified with carboxyl groups.

[0173] <Preparation of Abrasive Grains D>

[0174] After dispersing 1000 g of high-purity colloidal silica (code: PL-3; silica concentration of 20% by mass) manufactured by Fuso Chemical Industry Co., Ltd. in a mixed solvent of 100 g of pure water and 2850 g of methanol, 5.0 g of 3-aminopropyltrimethoxysilane was added and refluxed at boiling point for 4 hours. Thereafter, pure water was added to maintain the volume of the dispersion while replacing the methanol with water. When the tower top temperature reached 100°C, the addition of pure water was terminated and the dispersion was allowed to stand until the temperature was below 30°C. In this way, a dispersion containing 15% by mass of abrasive particles D was obtained, wherein the abrasive particles D had an average primary particle size of 46 nm, an average secondary particle size of 69 nm, and the silica surface was modified with amino groups.

[0175] <Measurement of average primary particle size and average secondary particle size>

[0176] The average primary particle size of abrasive particles A to D was calculated according to the method described in Japanese Patent Laid-Open No. 2004-315300. Specifically, the dispersion of the abrasive particles was pre-dried on a hot plate, heat-treated at 800°C for 1 hour, and the specific surface area was measured by nitrogen adsorption method (BET method, "BELSORP MR6" manufactured by Microtrac). The true specific gravity of silicon oxide was set to 2.2, and the primary particle size (nm) = 2727 / specific surface area (m 2 The average secondary particle size of the abrasive grains A to D was calculated by a dynamic light scattering method using "Zetasizer Ultra" manufactured by Malvern.

[0177] 3.2. Preparation of chemical mechanical polishing composition

[0178] The abrasives listed in Tables 1 and 2 were added to a polyethylene bottle of 10 L in a predetermined concentration, and each component was added to form the composition shown in Tables 1 and 2. The pH was adjusted to the pH shown in Tables 1 and 2 using an aqueous solution of ammonia (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name "aqueous ammonia"), and pure water was added as a liquid medium (B) to adjust the total amount of all components to 100% by mass, thereby preparing the chemical mechanical polishing compositions of each Example and each Comparative Example. For each chemical mechanical polishing composition obtained in the above manner, the zeta potential of the abrasive was measured using a zeta potential measuring device (manufactured by Malvern, model "Zetasizer Ultra"), and the obtained results are shown in Tables 1 and 2.

[0179] Evaluation methods

[0180] 3.3.1. Polishing speed evaluation

[0181] The chemical mechanical polishing composition obtained above was used to polish a 12-inch diameter belt. Silver film wafer, 12 inch diameter strip Tantalum nitride film wafers, 12-inch diameter strips Wafers having silicon oxide films of 300 nm and 100 nm were used as the processing objects, and a chemical mechanical polishing test was performed for 30 seconds under the following polishing conditions.

[0182] <Grinding conditions>

[0183] ■Grinding device: G&P Technology, model number POLI-762L

[0184] ■Polishing pad: IC1000XYP manufactured by NITTA DuPont

[0185] ■Chemical mechanical polishing composition supply rate: 300 mL / min

[0186] ■Platen speed: 87rpm

[0187] ■Head speed: 93rpm

[0188] ■Head pressing pressure: 2psi

[0189] ■

[0190] The thickness of the silver film and tantalum nitride film was measured by a resistivity measuring machine (manufactured by Kokusai Electric Semiconductor Service, model "VR300DEC") using a DC four-probe method, and the resistance was calculated using the following formula based on the sheet resistance value and the volume resistivity of the silver or tantalum nitride.

[0191]

[0192] The thickness of the silicon oxide film was calculated by measuring the refractive index using a non-contact optical film thickness measuring device (manufactured by SCREEN Holdings, model “VM-1310”).

[0193] The evaluation criteria of the polishing rate are as follows: Tables 1 and 2 show the polishing rates of the silver film, tantalum nitride film, and silicon oxide film, and the evaluation results of the polishing rates.

[0194] (Evaluation Criteria)

[0195] ■“A”… The polishing speed of the silver film is When the polishing time is 0.1777 W / min or more, the polishing time of wiring can be significantly shortened in actual semiconductor polishing, so it is judged to be good.

[0196] ■“B”…The polishing speed of the silver film is less than / min, the polishing rate was too low to be practically applicable, and was therefore determined to be poor.

[0197] 3.3.2. Determination of reflectivity of polished silver film

[0198] The chemical mechanical polishing composition obtained above was used to polish a 12-inch diameter belt. A wafer with a silver film was used as the processed object, and a chemical mechanical polishing test was performed for 30 seconds under the following polishing conditions. In the case of silver corrosion or polishing damage, the reflectivity of silver becomes low, so the corrosion and polishing damage of the polished surface of the silver film can be evaluated by evaluating the reflectivity.

[0199] <Grinding conditions>

[0200] ■Grinding device: G&P Technology, model number POLI-762L

[0201] ■Polishing pad: IC1000XYP manufactured by NITTA DuPont

[0202] ■Chemical mechanical polishing composition supply rate: 300 mL / min

[0203] ■Platen speed: 87rpm

[0204] ■Head speed: 93rpm

[0205] ■Head pressing pressure: 2psi

[0206] The reflectance at 459 nm was measured using a non-contact optical film thickness measuring device (manufactured by Filmetrics, model “F40-UV”).

[0207] The evaluation criteria for the reflectance of the silver film are as follows. The evaluation results are shown in Tables 1 and 2.

[0208] (Evaluation Criteria)

[0209] ■ "A" ... When the reflectance is 92% or more, the corrosion and polishing damage on the silver film surface are small and it is judged to be good.

[0210] ■ "B" ... When the reflectance is less than 92%, the silver film surface is much corroded or polished and is judged as defective.

[0211] 3.4. Evaluation results

[0212] Tables 1 and 2 show the compositions of the chemical mechanical polishing compositions of Examples and Comparative Examples and the results of evaluation.

[0213]

[0214]

[0215] The following commercial products or reagents were used for the components in Tables 1 and 2.

[0216] <Abrasive grains>

[0217] ■ Abrasive A: colloidal silica prepared above with a surface modified by sulfonic groups, average secondary particle size 38 nm

[0218] ■ Abrasive B: colloidal silica prepared above with a surface modified by sulfonic groups, average secondary particle size 68 nm

[0219] ■ Abrasive C: colloidal silica prepared above with carboxyl-modified surface, average secondary particle size 69 nm

[0220] ■ Abrasive particles D: colloidal silica prepared above with amino-modified surface, average secondary particle size 69 nm

[0221] ■PL-1: Made by Fuso Chemical Industries, ultra-high purity unmodified colloidal silica, average secondary particle size 40nm

[0222] ■PL-3: Made by Fuso Chemical Industries, ultra-high purity non-modified colloidal silica, average secondary particle size 70nm

[0223] <Oxidants>

[0224] ■ Hydrogen peroxide: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name "hydrogen peroxide"

[0225] <Nitrogen-containing heterocyclic compounds>

[0226] ■Benzotriazole: manufactured by Johoku Chemical Co., Ltd., trade name "BT-120SG"

[0227] ■2,2'-[[(Methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol: manufactured by Chengbei Chemical Co., Ltd., trade name "TT-LYK"

[0228] ■Carboxybenzotriazole: manufactured by Johoku Chemical Co., Ltd., trade name "CBT-SG"

[0229] ■1,2,4-Triazole: manufactured by Tokyo Chemical Industry Co., Ltd., trade name "1,2,4-Triazole"

[0230] ■1-(2,3-dicarboxypropyl)benzotriazole: manufactured by Chengbei Chemical Co., Ltd., trade name "BT-250"

[0231] <Acid>

[0232] ■Nitric acid: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name "Nitric acid (1.38)"

[0233] <Other additives>

[0234] (Basic Compounds)

[0235] ■Tetraethylammonium hydroxide: manufactured by Tokyo Chemical Industry Co., Ltd., trade name "Tetraethylammonium Hydroxide (10% in Water)"

[0236] (Water-soluble polymer)

[0237] ■ Polyacrylic acid: manufactured by Toa Gosei Co., Ltd., trade name "Julimar AC-10L"

[0238] ■Polyvinylpyrrolidone: manufactured by Tokyo Chemical Industry Co., Ltd., trade name "Polyvinylpyrrolidone K 15 Average Molecular Wt. 10000"

[0239] ■Polyethylene glycol: manufactured by Toho Chemical Industry Co., Ltd., trade name "PEG-400"

[0240] (Phosphate)

[0241] ■Polyoxyethylene allylphenyl phosphate amine salt: manufactured by Takemoto Oil & Fats Co., Ltd., trade name "NewKargen FS-3AQ" (20% aqueous solution)

[0242] (Organic Acid)

[0243] ■Citric acid: manufactured by Fuso Chemical Industries, trade name "Purified citric acid (crystals) L"

[0244] According to the chemical mechanical polishing compositions of Examples 1 to 12, it is found that the polished surface containing silver can be polished at high speed and the occurrence of corrosion or polishing damage on the polished surface after polishing can be effectively reduced, thereby obtaining a polished surface with excellent high reflectivity.

[0245] The chemical mechanical polishing compositions of Comparative Examples 1 and 3 have a Mc / Md value of less than 10 or do not contain the component (C). In such cases, it is found that the polishing rate of the silver film is significantly reduced.

[0246] The chemical mechanical polishing compositions of Comparative Examples 2 and 4 have a Mc / Md value of 200 or more or do not contain component (D). In such cases, it is found that corrosion or polishing scratches on the polished surface after polishing cannot be suppressed, and the reflectivity of the silver film decreases.

[0247] The chemical mechanical polishing compositions of Comparative Examples 5 and 6 are examples in which the absolute value of the zeta potential of component (A) is less than 10 mV. In this case, it is known that component (A) is easily aggregated, and the aggregated abrasive particles cause polishing damage on the silver film surface, and the reflectivity of the silver film decreases.

[0248] The present invention is not limited to the embodiments described, and various modifications are possible. For example, the present invention includes a structure that is substantially the same as the structure described in the embodiments (e.g., a structure with the same function, method, and result, or a structure with the same purpose and effect). In addition, the present invention includes a structure in which a non-essential part of the structure described in the embodiments is replaced. In addition, the present invention includes a structure that exerts the same effect as the structure described in the embodiments or a structure that can achieve the same purpose. In addition, the present invention includes a structure obtained by adding a known technology to the structure described in the embodiments.

[0249] Explanation of symbols

[0250] 10: Matrix

[0251] 12: Silicon oxide film

[0252] 14: Tantalum nitride film

[0253] 16: Silver film

[0254] 42: Slurry supply nozzle

[0255] 44: Slurry (chemical mechanical polishing composition)

[0256] 46: Polishing pad

[0257] 48: Turntable

[0258] 50: Semiconductor substrate

[0259] 52: Bearing head

[0260] 54: Water supply nozzle

[0261] 56: Dresser

[0262] 100: Processed object

[0263] 200: Grinding device

Claims

1. A chemical mechanical polishing composition comprising (A) abrasive particles, (B) Liquid medium, (C) an oxidizing agent, and (D) a chemical mechanical polishing composition comprising a nitrogen-containing heterocyclic compound, wherein The absolute value of the zeta potential of the component (A) in the chemical mechanical polishing composition is 10 mV or more, When the content of the (C) component is represented by Mc (mass %) and the content of the (D) component is represented by Md (mass %), Mc / Md=10-200.

2. The chemical mechanical polishing composition according to claim 1, wherein the component (A) has a functional group represented by the following general formula (1): <h2 style=";text-align:left;direction:ltr">-SO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> M<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ·····(1) (M + represents a monovalent cation). 3 . The chemical mechanical polishing composition according to claim 2 , wherein the zeta potential of the component (A) in the chemical mechanical polishing composition is −10 mV or less.

4. The chemical mechanical polishing composition according to claim 1, wherein the component (A) has a functional group represented by the following general formula (2): -COO - M + ·····(2) (M + represents a monovalent cation). 5 . The chemical mechanical polishing composition according to claim 4 , wherein the zeta potential of the component (A) in the chemical mechanical polishing composition is −10 mV or less.

6. The chemical mechanical polishing composition according to claim 1, wherein the component (A) has a functional group represented by the following general formula (3) or the following general formula (4), -NR 1 R 2 ·····(3) -N + R 1 R 2 R 3 M - ·····(4) (In the general formula (3) and the general formula (4), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, or a substituted or unsubstituted hydrocarbon group; M - represents anion). 7 . The chemical mechanical polishing composition according to claim 6 , wherein the zeta potential of the component (A) in the chemical mechanical polishing composition is +10 mV or more. The chemical mechanical polishing composition according to claim 1 , wherein the pH is 1 to 6. 9 . The chemical mechanical polishing composition according to claim 1 , wherein a content of the component (A) is 0.005 mass % or more and 15 mass % or less based on the total mass of the chemical mechanical polishing composition. 10 . The chemical mechanical polishing composition according to claim 1 , wherein the component (D) has an azole structure. 11 . A polishing method comprising the step of polishing a semiconductor substrate using the chemical mechanical polishing composition according to claim 1 . 12 . The polishing method according to claim 11 , wherein the semiconductor substrate includes a portion containing silver.

Citation Information

Patent Citations

  • Silica fine particle, silica colloid in which silica fine particles are dispersed and method of manufacturing the same

    JP2004315300A

  • Improved chemical-mechanical polishing slurry for polishing copper or silver films

    JP2005518669A

  • Method for producing neutral colloidal silica

    JP2007153732A

  • Grinding composition, grinding method using the same and manufacturing method of substrate

    JP2013121631A

  • Chemical mechanical polishing composition and method for passivating metals

    JP2014507799A